Health Workers’ Acceptance and Satisfaction on the Usability of the Digital Health Goods, in Kono District, Sierra Leone - Pognon PR; Boima F; Mekonnen ZA (Journal of Multidisciplinary Healthcare)
Pierre Ricard Pognon, Foday Boima, Zeleke Abebaw Mekonnen Strategic Health Information System, Partners in Health, Freetown, Sierra LeoneCorrespondence: Zeleke Abebaw Mekonnen, Research Specialist, Partners in Health, P.O. Box: 298, Freetown, Sierra Leone, Tel +23233615423, Email zelekeabebaw7@gmail.comIntroduction: Digital health systems implementation in developing countries is increasing exponentially, and digital health interventions are essential tools to improve healthcare access and quality. In contrast, the evidence base is meager about the acceptance and satisfaction of end users towards digital health goods. Hence, this study aims to evaluate the acceptance and satisfaction of end users on the usability of digital goods in Sierra Leone.Methods: Health facility-based cross-sectional study design was employed, and a total of 151 participants were included. Data were collected using a validated data collection tool. Initially, descriptive data analysis was done. Finally, bivariate and multivariate logistic regressions were applied to identify predictors for user acceptance of digital health goods. Finally, findings are presented as AORs along with 95% CIs.Results: The study considered 151 respondents for analysis. In this study, 72.2% with 95%  CI: 64.4– 78.8% of respondents have good acceptance of the digital health systems. The findings revealed that 49.7% and 45.7% of respondents were strongly satisfied and satisfied, respectively. The regression analysis indicated that perceived ease of use [AOR=5.56; 95% CI: 2.17, 14.26], digital health system type [AOR=0.18, 95% CI: 0.06, 0.55], and frequency of digital system use [AOR=0.04; 95% CI: 0.01, 0.41] were predictors of user acceptance. The major barriers for successful implementation were inability to be used offline, being slow, and taking longer time to input information in the digital systems.Conclusion: End user acceptance and satisfaction with digital health goods were high. Perceived ease of use, digital system type, and frequency of using digital systems are predictors of user acceptance. Major barriers to digital systems implementation include inability to be used offline and taking longer time to input information in the systems. Long-term system acceptance could be achieved through addressing end user preference and potential barriers of implementation.Keywords: user acceptance, technology acceptance model, satisfaction, digital health, Sierra Leone